Bibliometric Analysis for Research Trends Nanofiltration Membranes in The Past Decade to 2023 - Yurin Karunia Apsha Albaina Iasya; Asep Bayu Dani Nandiyanto (Indonesian Society of Limnology, 2023)
Water treatment is an important part that has an impact on life, to understand the progress of nanofiltration membrane research literature related to this field was obtained from the Google Scholar database. Based on mapping and visualization software VOSviewer, the number of publications and groupings were calculated and analyzed. Research advances and trends in the field of nanofiltration membranes are summarized. The results of the study show that since 2013 the quantity of publications in this field has increased every year until 2020 then decreased in 2021 and then increased again in 2022. This field has received attention including its wide application in water treatment. Related studies have been published in the journal of Membrane Science and Desalination which is the authoritative journal in this field with the largest number of publications. According to the keyword network map of nanofiltration membranes there are 8 clusters, and this field can generally be divided into three research stages, namely synthesis, characterization, and performance testing. To achieve the goals of research development, it must be further deepened in future work. This article will provide a reference for researchers engaged in membrane technology and its applications.